The psychometric properties of the ADHD rating scale—5 for children and adolescents, home version for Sudan - Al Jaffal, Mohammed; Becker, David; Alhossein, Abdulkarim; Bakhiet, Salaheldin Farah; Aldabas, Rashed; Abaoud, Abdulrahman; Abdu Elrahim, Nagda Mohamed; Alharthi, Hanan (Frontiers in Psychiatry, 2024)
There is a lack of universal scales for tracking ADHD symptoms in the home for children/adolescents in the Sudanese context. For this reason, this study aimed to validate the ADHD Rating Scale-5 for Children and Adolescents, Home Version (DuPaul et al., 2016) for use by parents in Sudan to assess their children for ADHD. This scale is widely used by parents to assess their children aged 5-17 years for ADHD in the home environment. The current study involved 3,742 Sudanese parents of school-aged children and adolescents, each asked to complete the instrument for one child in their family; only one parent per family participated in the study.. The authors then examined the psychometric properties of the scale from the completed assessments. The results indicated acceptable to high reliability for the total scale and both the symptom and impairment items. Exploratory and confirmatory factor analyses demonstrated high external and construct validity when applying the scale to the Sudanese sample. the factor structure resembled that of the normative U.S. sample in terms of the number of extractable factors and the strength of factor loadings. Based on the results, this adaptation of the home version of the ADHD Scale-5 for Children and Adolescents is both valid and reliable for use by Sudanese parents in the home environment.